Patterns of International Capital Raisings - Gozzi, Juan Carlos; Levine, Ross; Schmukler, Sergio L. (World Bank, Washington, DC, 2012)
This paper documents several new patterns associated with firms issuing securities in foreign markets that motivate the need for and help guide future research. Besides noting that these international capital raisings grew almost four-fold from 1991 to 2005, accounting for 35 percent of all capital raised through security issuances, the paper has three main findings. First, a large and growing fraction of capital raisings, especially debt issuances, occurs in international markets, but a very small number of firms accounts for the bulk of international capital raisings, highlighting the distributional implications of financial globalization. Second, changes in firm performance following equity and debt issuances in international markets are qualitatively similar to those following domestic issuances, suggesting that capital raisings abroad are not intrinsically different from domestic ones. Third, after firms start accessing international markets, they significantly increase the amount raised in domestic markets, suggesting that international and domestic markets are complements.